2005
DOI: 10.1038/ni1186
|View full text |Cite
|
Sign up to set email alerts
|

TIM-1 induces T cell activation and inhibits the development of peripheral tolerance

Abstract: We have examined the function of TIM-1, encoded by a gene identified as an 'atopy susceptibility gene' (Havcr1*), and demonstrate here that TIM-1 is a molecule that costimulates T cell activation. TIM-1 was expressed on CD4(+) T cells after activation and its expression was sustained preferentially in T helper type 2 (T(H)2) but not T(H)1 cells. In vitro stimulation of CD4(+) T cells with a TIM-1-specific monoclonal antibody and T cell receptor ligation enhanced T cell proliferation; in T(H)2 cells, such costi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
326
5
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(350 citation statements)
references
References 26 publications
18
326
5
1
Order By: Relevance
“…Tim-3 has been proposed to be a novel candidate target for the treatment of SLE. [32][33][34][35][36][37] Unlike the other Tim molecules, Tim-4 is exclusively expressed in APCs and it is unclear to date whether Tim-4 plays a role in SLE pathogenesis. Due to the lack of a directly labeled anti-human Tim-4 antibody, it is difficult to quantitate Tim-4 protein on APCs by flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…Tim-3 has been proposed to be a novel candidate target for the treatment of SLE. [32][33][34][35][36][37] Unlike the other Tim molecules, Tim-4 is exclusively expressed in APCs and it is unclear to date whether Tim-4 plays a role in SLE pathogenesis. Due to the lack of a directly labeled anti-human Tim-4 antibody, it is difficult to quantitate Tim-4 protein on APCs by flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that TIM-1 mRNA and protein are expressed in both mouse (1,11,18) and human (14,19) CD4 ϩ T cells following activation. To study the downstream signaling effects of TIM-1 expression in human T cells, multiple immortalized lines from ATCC and elsewhere were tested for TIM-1 expression by FACS analysis, but no TIM-1-positive cell lines were found (data not shown).…”
Section: Tim-1 Overexpression Induces T Cell Activation Signalsmentioning
confidence: 99%
“…For example, studies of TIM-1 responses induced by an anti-murine TIM-1 mAb or by murine TIM-4, a putative TIM-1 ligand, showed that engagement of TIM-1 up-regulated cellular proliferation and the expression of Th1 and Th2 cytokines both in vitro and in vivo (11,12). However, administration of the TIM-1-Fc fusion protein to mice also upregulated immune responses (12), a result seemingly at odds with the proposed model of TIM-1 action.…”
mentioning
confidence: 99%
“…Anti‐TIM‐1 antibody (Clone RMT1‐10) ameliorates Experimental autoimmune encephalomyelitis (EAE),17 allergic asthma,37 glomerulonephritis38 and corneal allograft rejection 39. In contrast another anti‐TIM‐1 antibody (clone 3B3) enhances T cell proliferation and Th2 effector function 17, 40, 41. HFD‐fed LDLR‐deficient mice treated with anti‐TIM‐1 antibody (clone 3D10) accelerated atherosclerosis by ≈50% via increased aortic CD4 T cells 42.…”
Section: Discussionmentioning
confidence: 99%